A resident-led project to improve documentation of overweight and obesity in a primary care clinic. Issue 5 (3rd September 2019) - Wang'ondu, Ruth; Vitale, Rebecca; Rosenblum, Hannah; Pinto-Taylor, Emily; Grossman, Matthew; Sharifi, Mona; Gielissen, Katherine; Doolittle, Benjamin
ABSTRACT: Background : Although the prevalence of overweight and obesity (OW/OB) has increased in the last three decades, studies show that these conditions are sub-optimally documented by physicians. Health information technology tools have varying effects on improving documentation of OW/OB but often have to be complemented with other interventions to be effective. Objective : Upon identifying low rates of documentation of diagnoses of overweight and obesity by resident and attending physicians, despite the use of an electronic health record (EHR) with automated BMI calculations, we performed a quality improvement (QI) project to improve documentation of these diagnoses for patients in our community hospital primary care clinic. Methods : The EHR was reviewed to determine documentation rates by resident and attending physicians between 1 March 2018 and 31 September 2018. We collected pre-intervention data, developed interventions, and implemented tests of change using Plan-Do-Study-Act (PDSA) cycles to improve documentation of OW/OB. Results : Documentation of overweight and obesity diagnoses increased from a baseline of 46% to 79% over a 20-week period after initiation of our project. Conclusion : We demonstrate the successful implementation of resident-led, multi-faceted interventions in a team-based QI project to optimize documentation of OW/OB in the EHR.